Pseudomonas aeruginosa alkyl quinolone response is dampened by Enterococcus faecalis - Maggie M. Fink; Abigail A. Weaver; Dharmeshkumar Parmar; Jon E. Paczkowski; Lingyun Li; Maggie K. Klaers; Ella A. Junker; Elizabeth A. Jarocki; Jonathan V. Sweedler; Joshua D. Shrout (mBio)
ABSTRACT The bacterium Pseudomonas aeruginosa is an opportunistic pathogen that can cause lung, skin, wound, joint, urinary tract, and eye infections. While P. aeruginosa is known to exhibit a robust competitive response toward other bacterial species, this bacterium is frequently identified in polymicrobial infections where multiple species survive. For example, in prosthetic joint infections, P. aeruginosa can be identified along with other pathogenic bacteria including Staphylococcus aureus, Enterococcus faecalis, and Corynebacterium striatum. Here, we have explored the survival and behavior of such microbes and find that E. faecalis readily survives culturing with P. aeruginosa while other tested species do not. In each of the tested conditions, E. faecalis growth remained unchanged by the presence of P. aeruginosa, indicating a unique mutualistic interaction between the two species. We find that E. faecalis proximity leads P. aeruginosa to attenuate competitive behaviors as exemplified by reduced production of Pseudomonas quinolone signal and pyocyanin. Reduced alkyl quinolones are important to E. faecalis as these will grow in supernatant from a quinolone mutant but not P. aeruginosa wild-type in planktonic culture. The reduced pyocyanin production of P. aeruginosa is attributable to production of ornithine by E. faecalis, which we recapitulate by adding exogenous ornithine to P. aeruginosa monocultures. Similarly, co-culture with an ornithine-deficient strain of E. faecalis leads P. aeruginosa to yield near monoculture amounts of pyocyanin. Here, we directly demonstrate how notorious pathogens such as P. aeruginosa might persist in polymicrobial infections under the influence of metabolites produced by other bacterial species.IMPORTANCEWhile we now appreciate that many infections are polymicrobial, we understand little of the specific actions between a given set of microbes to enable combinatorial survival and pathogenesis. The bacteria Pseudomonas aeruginosa and Enterococcus faecalis are both prevalent pathogens in wound, urinary tract, and bacteremic infections. While P. aeruginosa often kills other species in standard laboratory culture conditions, we present here that E. faecalis can be reliably co-cultured with P. aeruginosa. We specifically detail that ornithine produced by E. faecalis reduces the Pseudomonas quinolone signal response of P. aeruginosa. This reduction of the Pseudomonas quinolone signal response aids E. faecalis growth.